Plasminogen Activator Inhibitor-1 Is the Primary Inhibitor of Tissue-Type Plasminogen Activator in Pregnancy Plasma - Jørgensen, Maja; Philips, Malou; Thorsen, Sixtus; Selmer, Johan; Zeuthen, Jesper (Thrombosis and Haemostasis, 1987)
The aim of the present work was to clarify to what extent plasminogen activator inhibitor-1 (PAI-1) and plasminogen activator inhibitor-2 (PAI-2) contribute to the increase in plasma inhibition of tissue-type plasminogen activator (t-PA) observed during pregnancy. It was demonstrated that a monoclonal antibody against PAI-1 almost completely quenched inhibition of single-chain t-PA and most of the inhibition of two-chain t-PA in plasma during the third trimester of piegnancy. The remaining inhibition of two-chain t-PA was to a great extent abolished by a PAI-2 antibody. The second order rate constant (k1) for inhibition of single-chain t-PA by the inhibitor neutralized by the PAI-1 antibody was about 4.8 · 106 M-1 · s-1. The conversion of singlechain t-PA to the two-ehain form increased the reaction rate with the inhibitor about 3-fold. These kinetic data are compaiable with those obtained with TAI-l in non-pregnancy plasma oi with purified PAI-1. From the above results it is concluded that PAI-1 is the primary inhibitor of both single-chain and two chain t PA and that PAI-2 is the secondary inhibitor of two-chain t-PA in pregnancy plasma. The concentration of reactive PAI-1 versus gestation age was assayed in plasma from 6 women by binding of PAI-1 to 125I-labelled single-chain t-PA followed by quantitation of the labelled t-PA-PAI-1 complex after separation by SDS- polyacrylamide gel electrophoresis. It was found that the concentration of PAI-1 increased 4 to 8-fold during the gestation period reaching a level of about 1.4 nM at term. Post partum the plasma concentration declined abruptly within 24 h to the level observed in age-matched non-pregnant women.
Keywords: Plasma; Plasminogen activator inhibitor-1; Plasminogen activator inhibitor-2; Pregnancy; Tissue-type plasminogen activator